MATHEMATICAL MODELING OF CHEMICALTECHNOLOGICAL PROCESSES, DATA PROCESSING - Turayev Kahramon Nortojiyevich (Western European Studies, 2024)
The article describes the mathematical modeling of chemical-technological processes and the scientific-methodological processes carried out in this regard
Keywords: Simulation; experiments; optimization